MODERN CAREER THEORIES IN THE CONTEXT OF DIFFERENT GENERATIONS AND CHANGEABLE ENVIRONMENT - Katane, Irēna; Korna-Opincāne, Evita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
One the most topical issues in modern education is to support students in their interaction with the changing environment, thus helping them to accept these changes, live with them and find new opportunities for development, including opportunities for career development within these changes. Another topical issue is the generational change of students and respecting the specific qualities of this new generation during the education and career development support process in schools. Both these issues reflect in career theories in a form of new trends. Which generations can these career theories be applied to the most? How will the representatives of different generations join in the changing educational and professional environments? Understanding of these questions is essential within the context of providing modern career support. The aim of this article is to analyse and evaluate modern career theories within the context of different generations and changeable environment. The publication comprises the finding of the latest theoretical studies and results of the authors reflecting upon their professional experience. Career development during the current decade of the 21st century is determined by several new theoretical viewpoints, each of which focuses on its own research issue, yet they are united in the aspect of taking individual responsibility of one’s own career development and career self-management in the situation of changeable  environment, which can be helpful in adapting to and coping with unexpected changes and challenges presented therewith in the context of career development. From the point of view of modern career theories, challenges within educational and professional environments posed by global changes may be better understood within the context of career development of pupils. People of different generations have different attitudes towards their careers and the possibilities for their developments, therefore studies within the context of generation and career theories are essential.